Young Adult With Osteosarcoma of the Mandible and the Challenge in Management: Review of the Pediatric and Adult Literatures. Issue 1 (January 2019) - Kuo, Christopher; Kent, Paul M.
Abstract : Neoadjuvant chemotherapy for osteosarcoma of the jaw (OSJ) remains controversial despite being a standardized treatment in osteosarcoma of the long bones. We present a case of a 22-year-old male with OSJ and performed a retrospective systemic review of previously published literatures of OSJ. We identified 27 articles: 7% recommended neoadjuvant chemotherapy, 22% recommended adjuvant chemotherapy, 19% recommended both neoadjuvant and adjuvant chemotherapy, 33% recommended against chemotherapy and 19% stated the role of chemotherapy is unknown. The lack of consensus regarding the use of chemotherapy in OSJ, despite its benefits, demonstrates the need to establish a standardized algorithm for OSJ.